Comparison of the Effectiveness of Olson's Marital Enrichment Training, Lazarus's Multimodal Therapy, and Islamic Approach-Based Marital Skills Training on Marital Satisfaction and Conflicts among Couples - Lotfi, Zahra; Salarifar, Mohammad Reza; Shivandi Cheliche, Kamran (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to compare the effectiveness of Olson's marital enrichment training, Lazarus's multimodal therapy, and Islamic approach-based marital skills training on marital satisfaction and conflicts among couples.Methods: The present study is applied in terms of its objective and quasi-experimental with a pretest-posttest design, involving three experimental groups and one control group. The statistical population included couples who referred to psychology centers and clinics in Isfahan during the second half of 2023. Among them, 80 participants (40 couples) with low compatibility and dissatisfaction with marital life were selected using a non-random convenience sampling method. They were then randomly and equally divided into four groups of 20 individuals (10 couples per group). The measurement tools included the Enrich Marital Satisfaction Questionnaire (Fowers & Olson, 1998), the Marital Conflict Questionnaire (Sanaei & Barati, 2008), and the intervention packages for multimodal therapy based on Lazarus's approach, Olson's marital enrichment program, and Islamic approach-based marital skills training (Salarifar, 2021). Each experimental group underwent eight 90-minute training sessions.Findings: The results indicated that all three educational-therapeutic packages were effective in reducing conflicts and increasing marital satisfaction.Conclusion: Based on the findings of this study, it is recommended that qualitative research be conducted to identify the factors contributing to marital dissatisfaction and conflicts. Subsequently, any of these three therapeutic and educational approaches can be utilized for more in-depth resolution of couples' issues.